The Geographies of Second-generation Muslim Women: Identity Formation and Everyday Experiences in Public Space - Lagasi, Alisha C. (Université d'Ottawa / University of Ottawa, 2013)
This project is interested in the ways that second-generation Muslim women experience public space, in particular with respect to how their identities and sense of belonging are shaped through everyday encounters in public. This implicates the reactions and behaviours of strangers who they meet in public, their own bodily comportment, and the ideas and values communicated by their parents and other co-ethnics about women’s place in public space, as well as the ways that religiosity may enhance or hinder everyday belonging. Through the use of qualitative, one-on-one interviews, this research seeks to investigate daily experiences within Ottawa, Canada, particularly with respect to how such interactions inform a sense of (dis)comfort and belonging in public space in Canadian society. Moreover, this project is interested in the negotiation that many second-generation Muslim women undertake between family and ethno-religious community values and those of mainstream Canadian society in urban public spaces. In order to address these topics, the study examines Muslim women’s everyday experiences in public – the ways in which visibility and generational status can influence daily encounters and (dis)comfort, as well as women’s ability to actively negotiate their identity and belonging through engagement with strangers and acquaintances.
Keywords: public space; identity; Islam; second generation; gender; discomfort